Aqīdah in the Digital Age: Social Media, Religious Authority, and an Islamic Legal Framework - Manzoor Ahmed Kalwar; Danyal Ahmad; Hafiza Sana Rehman Khan; Najmul Sahar Ilyas (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2026)
Purpose - The rapid growth of digital technology and social media has significantly impacted how religious knowledge is accessed, interpreted, and practised among Muslim youth. Concurrently, this shift has contributed to the decentralisation of religious authority in Indonesia, raising concerns about the authenticity, consistency, and integrity of Islamic creed (ʿaqīdah) within largely unregulated digital environments. Although existing literature has predominantly examined these developments through sociological and media perspectives, limited attention has been given to their implications within Islamic legal and theological paradigms. This study aims to examine the role of digital platforms in the formation, negotiation, and maintenance of ʿaqīdah among Muslim youth, while also analysing these dynamics through the lens of Islamic jurisprudence.Methodology/approach - To achieve this, the research employs a qualitative method, combining a comprehensive literature review with thematic analysis, supported by selected case examples of Islamic digital preaching (daʿwah) movements in Indonesia. The analytical framework is grounded in key Islamic legal concepts, including verification (tabayyun), ethical responsibility (amānah), the authority of qualified scholars, and the overarching framework of the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the preservation of religion (ḥifẓ al-dīn).Findings - The findings reveal that digital media has restructured Islamic discourse: it has made it more participatory and accessible; yet, it has also facilitated misinformation, fragmented knowledge, and contributed to the erosion of traditional authority structures. These dynamics present both opportunities and challenges. On the one hand, they enable broader access to religious education; on the other, they pose risks to the integrity of ʿaqīdah. The study concludes that digital religious interaction must be guided by an Islamic legal-ethical framework to safeguard doctrinal integrity.Conclusion - This research contributes a normative-analytical framework that bridges Islamic theology, sociology, and jurisprudence. It further recommends strengthening digital religious literacy, enhancing the presence of qualified scholars in online spaces, and establishing ethical standards for digital religious discourse.